ASMAUL HUSNA DALAM LUKISAN KALIGRAFI ARAB DENGAN KHAT FARISI DAN KHAT TSULUTS - FINA SAPRIANI, Dr. Budiwirman, M.Pd, Drs. Syafei,M.Ag (Serupa The Journal of Art Education, 2014)
Humans have a different view of life, but human life should have the same guidelines. Especially man must believe in Allah. Beautiful Names are good names for Allah, as proof of his kemahaagungan and perfection. The purpose and goal of his is to visualize the Beautiful Names in Arabic Calligraphy Painting by KhatKhatTsuluts Pharisee And, with the aim that people always remember his greatness through Arabic calligraphy and handwriting khat- know about the beauty of Arabic calligraphy, especially the Pharisees and KhatkhatTsuluts. The techniques or methods used to mature the use of color to reinforce the character on the object itself and based on the elements and principles of art using calligraphy handwriting on each work with one verse AsmaulHusna. The author expects the presence of works made can increase knowledge and insight on the author himself, armed from existing experiences that gave birth to works of Arabic calligraphy painting with its main object clause is Beautiful Names.Kata Kunci : Allah, Asmaul Husna, Lukisan, Kaligrafi.